ANALISIS PENGARUH CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL (Studi Kasus pada Perusahaan Wholesale dan Retail Trade yang Terdaftar di BEI Tahun 2010-2014) - Kirana, Maria Nindya; Wahyudi, Sugeng (Faculty of Economics and Business Diponegoro University, 2016)
The purpose of this study is to analyze the influence between Corporate Governance and Firm Financial Performance. Corporate Governance in this study is represented by Board of Commissioner, Proportion of Independent Commissioner, Audit Committee and Leverage. Firm’s Financial Performance is measured by using ROA. This study also uses firm size as a controlling variable. The sample used in this study is wholesale and retail trade firms listed in Indonesian Capital Market in 2010-2014. The sample were obtained by using the purposive sampling method and resulted 40 sample firms. The data used in this study collected from Indonesian Capital Market Directory and IDX. This research uses multiple regression analysis to analyze the data.The result revealed that the independent variables and control variable simultaneously affecting ROA. Board of Commissioner and Audit Committee are significantly impact ROA in positive way. While Proportion of Independent Commissioner and Leverage are significantly impact ROA in negative way.